Community-Based Paralegals for Access to Justice in Indonesia - Maharani, Marsha; Budiarti, Arsa Ilmi; Puteri, Bunga Pertiwi Tontowi; Arianto, Gladys Nadya (Advanced Studies on Socio-Economy Development, 2024)
Legal aid is an essential instrument in the criminal justice system, primarily to protect the human rights of the person who faces a trial. In 2019, The Indonesian Access to Justice Index identified the biggest problem in implementing legal aid: the distribution of lawyers due to the lack of understanding of the right to legal aid. Building on this research, the author found that most Indonesians prefer to seek legal help from non-formal legal assistance, such as family members, friends, and prominent community leaders, rather than formal legal assistance. Therefore, reducing the gap in people's capacity to maximize legal empowerment by increasing the number of paralegals in the Indonesian community is crucial. This article examines how community-based paralegals can significantly empower vulnerable communities and enhance strategic access to justice. Through the lens of social capital theory by Robert D. Putnam, this article argues that community-based paralegals can strengthen bonding social capital by empowering the community from within and reinforcing social ties among its members, and enhance bridging social capital by building external networks and opening access to information and resources that can support community welfare. Again, community-based paralegals offer a vital and effective alternative to traditional lawyers, mainly where legal professionals are scarce and unaffordable. Keywords: Access to Justice, Community-Based Paralegals, Legal, Marginalized Communities